ATP Citrate Lyase from Germinating Castor Bean Endosperm: Localization and some Properties - Fritsch, Hansjörg (1979)
ATP citrate lyase (EC 4.1.3.8) has been found in crude extracts from endosperm tissue of germinating castor bean and shows its maximum activity in 4- to 5-day-old seedlings. A strict requirement for coenzyme A and adenosine 5′-triphosphate was demonstrated. The pH optimum for the reaction is around 7.5. The unstable enzyme can be stabilized by freezing and addition of citrate and glycerol. (−)-Hydroxycitrate is a potent inhibitor. The molecular weight is about 400,000. The adenosine 5′-triphosphate citrate lyase is localized in the plastids, where it possibly plays a role in providing acetyl coenzyme A for lipid biosynthesis.